2021
DOI: 10.3389/fonc.2021.738961
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Action of Curcumin on High Glucose-Induced Chemoresistance in Hepatic Carcinoma Cells

Abstract: Along with direct anticancer activity, curcumin hinders the onset of chemoresistance. Among many, high glucose condition is a key driving factor for chemoresistance. However, the ability of curcumin remains unexplored against high glucose-induced chemoresistance. Moreover, chemoresistance is major hindrance in effective clinical management of liver cancer. Using hepatic carcinoma HepG2 cells, the present investigation demonstrates that high glucose induces chemoresistance, which is averted by the simultaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Lee and his college reported that no cytotoxicity was observed in HepG2 cells when curcumin was not more than 20 μM for 48 h treatment [ 60 ]. But Soni and his college reported that 10 μM curcumin sufficiently and significantly decreased the cell viability of HepG2 cells [ 61 ]. In line with Lee’ s result, our results showed that the lower dose (from 0 μM to 10 μM) curcumin has no significant effect on decreasing cellular viability of HepG2.2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and his college reported that no cytotoxicity was observed in HepG2 cells when curcumin was not more than 20 μM for 48 h treatment [ 60 ]. But Soni and his college reported that 10 μM curcumin sufficiently and significantly decreased the cell viability of HepG2 cells [ 61 ]. In line with Lee’ s result, our results showed that the lower dose (from 0 μM to 10 μM) curcumin has no significant effect on decreasing cellular viability of HepG2.2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…17 Curcumin has been shown to affect metabolism, resulting in lower glucose absorption and lactate generation. 18 Changes in metabolic pathways, particularly fatty acid metabolism, have been linked to phytocompounds such as resveratrol, quercetin, and epicatechin gallate. Our results show quercetin, curcumin and resveratrol, induce metabolic changes in Glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“… Vick et al (1973) introduced the first herbal GLUT inhibitor named “Phlorizin,” which was followed by a series of discoveries of several other GLUT inhibitors of plant origin which belong to various chemical categories, including alkaloids, flavonoids, and other oxygen heterocyclic and phenolic compounds ( Shriwas et al, 2020 ). Among these diverse categories of GLUT inhibitors of plant origin, those identified with antineoplastic action include more than 25 compounds, to name a few of them: apigenin ( Gonzalez-Menendez et al, 2014 ), curcumin ( Gunnink et al, 2016 ; Soni et al, 2021 ), genistein ( Vera et al, 1996 ; Pérez et al, 2011 ), naringenin ( Memariani et al, 2021 ), oridonin ( Yao et al, 2017 ), phloretin ( Wu et al, 2018 ; Wang et al, 2022 ), phlorizin ( Vick et al, 1973 ; Kwon and Levine, 2007 ; Shriwas et al, 2020 ), quercetin ( Schmidl et al, 2021a ), resveratrol ( Jung et al, 2013 ; Gwak et al, 2015 ; Zambrano et al, 2019 ; Samec et al, 2020 ), silybin ( Zhan et al, 2011 ), and vinblastine ( Shriwas et al, 2020 ). Although many of these GLUT inhibitors display a promising antineoplastic potential, the precise mechanism of the inhibitory action of most remains elusive, which needs to be deciphered for their optimal utilization in antineoplastic therapeutics.…”
Section: Inhibition Of Glut As a Promising Anti-cancer Approachmentioning
confidence: 99%